Fisioterapia respiratoria en la enfermedad pulmonar intersticial del adulto mayor. - Erika Paola, Herrera Vilema (2021)
This research project was carried out through a compilation of scientific articles on Respiratory Physiotherapy in interstitial lung disease, which specifies the effects and benefits of the different respiratory physiotherapy techniques applied to each patient. These studies were also applied in different types of interstitial lung disease, gender, stage of the disease, and age. The project systematized a search of 105 scientific articles, of which 40 were selected according to the inclusion and exclusion criteria. An evaluation of each article was carried out through the Pedro scale. In this research project, five scientific articles were selected, which were published in recent years, including articles in English and Spanish. The search for scientific articles was carried out through the following databases such as Scielo, ScienceDirect, Researchgate, BMJournals, and PubMed, with updated information which has gained greater relevance and scientific support at this time. Moreover, a search was made in different books to write part of the introduction and better knowledge. Results showed that all the authors agree on the benefits that Respiratory Physiotherapy provides in interstitial lung disease, regardless of age and gender. Thus, improving daily activities and the patient's quality of life, having higher care for the elderly since it is a vulnerable population, is why the prescription of respiratory physiotherapy must be personalized according to each patient's needs.